2012
DOI: 10.1111/j.1538-7836.2011.04570.x
|View full text |Cite
|
Sign up to set email alerts
|

The gain‐of‐function variant allele CYP2C19*17: a double‐edged sword between thrombosis and bleeding in clopidogrel‐treated patients

Abstract: Summary. Background: A large number of clinical studies have documented that a loss-of-function variant CYP2C19*2 affects clinical profiles of clopidogrel (efficacy and safety). However, data on the impact of a gain-of-function variant CYP2C19*17 on the response to that drug seem to be less consistent. Objectives: To systematically summarize all available clinical data assessing the role of the CYP2C19*17 variant in patients taking clopidogrel. Methods: A literature search was conducted and a meta-analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
3
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 36 publications
1
74
3
3
Order By: Relevance
“…That the *17 allele is associated with increased CYP2C19 activity is further supported by a number of studies showing a gene-dose effect, with *17/*17 patients having the greatest antiplatelet effect (lowest ontreatment platelet reactivity), with intermediate effects for *1/*17 relative to *1/*1 Harmsze et al, 2012;Li et al, 2012). A recent meta-analysis of *17 found that only 38% of *17 carriers have high on-treatment platelet reactivity compared with 51% of noncarriers (P = 0.0003) .…”
Section: B Cyp2c19 Genetic Polymorphismsmentioning
confidence: 69%
See 1 more Smart Citation
“…That the *17 allele is associated with increased CYP2C19 activity is further supported by a number of studies showing a gene-dose effect, with *17/*17 patients having the greatest antiplatelet effect (lowest ontreatment platelet reactivity), with intermediate effects for *1/*17 relative to *1/*1 Harmsze et al, 2012;Li et al, 2012). A recent meta-analysis of *17 found that only 38% of *17 carriers have high on-treatment platelet reactivity compared with 51% of noncarriers (P = 0.0003) .…”
Section: B Cyp2c19 Genetic Polymorphismsmentioning
confidence: 69%
“…Accumulating evidence for CYP2C19 and clopidogrel, and some inconsistencies in study results, led to a series of metaanalyses since 2010. Meta-analyses published since 2010 are summarized in Table 2 (Hulot et al, 2010;Mega et al, 2010;Bauer et al, 2011;Holmes et al, 2011;Liu et al, 2011;Sofi et al, 2011;Li et al, 2012;Zabalza et al, 2012). As is evident based on the samples sizes for the various meta-analyses, a variety of approaches have been taken in selection of studies to be included in the analysis.…”
Section: B Cyp2c19 Genetic Polymorphismsmentioning
confidence: 99%
“…On the other hand, CYP2C19*17 allele has been associated with enhanced clopidogrel response and increased risk of bleeding in some studies. [25][26][27][28] Variants in other genes, including ABCB1, CES1, and PON1, have been suggested to play a role in the interindividual variability of clopidogrel response, but these results have not been widely replicated. 27,29,30 A further weakness is that we were unable to include data in relation to medical or other treatments during the time period in the hospital with information on treatment coming entirely from redemption of prescriptions from community pharmacies.…”
Section: Discussionmentioning
confidence: 80%
“…It is, especially, unclear how gain-of-function alleles compensate against loss-of-function alleles in the same gene to affect outcomes. 44 Even the alleles in VKORC1 and CYP2C9 commonly used for predicting warfarin dosing account for o40% of the INR dosing variation, 45,46 and rare and private mutations in known pharmacogenomic genes have recently been reported to account for unexplained genetic variability. 47 This incomplete understanding of the genetic impact on drug outcomes is likely to affect the confidence of physicians and patients to genetic testing, as it reduces the process of clinical decision-making to an interpretation of probabilities and likelihoods.…”
Section: Imperfect Understanding Of Genetic Determinants Of Drug Respmentioning
confidence: 99%